The Timing of Prison Sanctions and the Odds of Returning to Prison After Release - D’Amato, Christopher (Crime & delinquency, 2022)
A sample of 48,930 inmates was examined to estimate the direct and moderating effect of the timing of prison sanctions on recidivism. Logistic regression models demonstrated that number of sanctions was positively associated with recidivism but timing of an inmate?s last sanction before release did not significantly influence recidivism. However, timing of an inmate?s last sanction moderated the association between number of sanctions and recidivism. This moderation effect suggested that as time between an inmate?s last sanction and release from prison increased, the effect of the total number of sanctions on recidivism decreased in magnitude. The results of this assessment suggest that the number and timing of sanctions matter in explaining the relationship between prison sanctions and recidivism.